Penggunaan Digital Marketing melalui Kegiatan Lelang Guna Meningkatkan Penjualan UMKM di Kelurahan Sukapura - Mahadianto, Moh. Yudi; Maulina, Rima; Yudistira, Elip; Lutfiyanah, Pepi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
MSMEs (Micro, Small and Medium Enterprises) have a very important role in the Indonesian economy, contributing 60% of GDP and absorbing 97% of the workforce. However, many MSMEs in Kelurahan Sukapura face challenges in digitally marketing their products, resulting in low sales. This research aims to improve the knowledge and skills of MSME players in digital marketing through online auction activities. Using a qualitative approach, this research involved MSME players who utilize social media such as Facebook, Instagram, and WhatsApp to expand their marketing networks. The one-month training provided an understanding of the importance of digital marketing and how to conduct online auctions. This training is expected to improve product design and photo skills, as well as expand market reach. The results of the socialization activities show that more than 60% of Indonesia's population has made purchases through e-commerce platforms, which signifies great potential for MSMEs to utilize online auction platforms to increase the visibility of their products. Through this research, it is hoped that MSME players in Sukapura Village can overcome the marketing problems they face and increase the purchasing power of the community for their products. The success of this program confirms the importance of education and training in developing the economic potential of communities in the digital era.